Associations of Hypertension Status with Physical Fitness Variables in Korean Women - Jin-Ho Yoon; Wi-Young So (Tehran University of Medical Sciences, 2013)
Background: In Korea, hypertension has become more prevalent with the Westernization of Korean diets and lack of exercise. This study aimed at investigating the associations between physical fitness variables and hypertension status in Korean women.Methods: The subjects were 9,216 women aged >20 years who visited a public health promotion center for physical fitness tests. Cardiovascular respiratory fitness was evaluated using VO2max, resting heart rate (RHR), double product (DP), and vital capacity and coordination-related physical fitness was measured using grip strength, number of sit-ups completed, sit-and-reach score, vertical jump height, number of side steps performed, and 1-leg standing with eyes open.Results: The prevalence rates of prehypertension and hypertension were 30.3% and 12.9% in this study, respectively. After adjusting for age, body mass index, drinking frequency, smoking intensity, and exercise intensity, the odds ratios (95% confidence interval) were calculated, and no statistically significant association was found between hypertension and physical fitness as measured by grip strength (P = 0.056), number of sit-ups completed (P = 0.140), and vertical jump height (P = 0.121). However, significant associations were found between hypertension and VO2max (P < 0.001), RHR (P < 0.001), DP (P < 0.001), vital capacity (P < 0.001), sit-and-reach score (P = 0.012), the number of side steps performed (P = 0.001), and 1-leg standing with eyes open (P < 0.001).Conclusion: We found that all the cardiovascular respiratory fitness variables and half of the motor- and coordination-related physical fitness variables were closely related with hypertension status.